Unfadeable - Broaddus, Maurice (Katherine Tegen Books, 2022)
Bella "Unfadeable" Fades is a graffiti artist who regularly tags walls and bridges in her Indianapolis neighborhood, the Land. She plans on laying low this summer in order to keep social services from learning that she's living on her own, but when she learns someone is misusing the funds for her neighborhood, she knows she can't stand by. Getting involved means she has to learn how to trust some of her neighbors, and she soon finds herself making a few enemies along the way. Bella realizes that taking risks and forming connections isn't such a bad thing as she tries to save her neighborhood.